The role of big-five personality and types of social media on perceived risk - Anggarani, Fadjri Kirana; Mardhiyah, Zahrina; Dewi, Claudia Rosari; Safithri, Trisnia Rizqi; Andreina, Sherly Rachma; Maisaroh, Rizqi; Pratiwi, Yovita Ajeng; Elmawati, Anjani (Indigenous, 2022)
Abstract. The infodemic spread during the last pandemic situation, and each individual's perceived risk varies based on the dominance of his/her personality. This study, therefore, aims to examine the effect of the Big-Five Personality and social media on the perceived risk in the vulnerable group. The number of subjects was 267 respondents from adolescence to late adulthood, with inclusion criteria: (1) active users of social media, (2) over 19 years old, and (3) approved informed consent. The research consisted of two study stages: quantitative and qualitative. The instruments used in the quantitative stage were (1) the social media questionnaire, (2) the Big-Five Inventory (BFI) scale, and (3) the perceived risk scale, while the instrument employed in the qualitative stage was an interview guideline with an open questionnaire. Then, quantitative data analysis used regression techniques, whereas qualitative ones utilized content technique analysis. As a result, the Big-Five Personality and the types of social media simultaneously and significantly affected perceived risk (p0.05). According to the qualitative method results, the information topic "Covid-19 Data Case" became a popular theme (37.83%), and the majority of respondents considered Covid-19 "very risky" (35.33%). In conclusion, neuroticism, YouTube, and WhatsApp have a role in perceived risk in vulnerable groups. On the other hand, YouTube posed the highest perceived risk compared to other social media. In addition, although the intensity of social media use did not affect perceived risk, the content about "Covid-19 Case Data" gave rise to the perception that Covid-19 was "very risky."Keywords: big-five personality; infodemic; perceived risk; types of social media.